Role-Playing Pedagogy for Disaster Mitigation Literacy among Child Hydrometeorological Hazard Survivors - Putri Khayriani; Syarfina Syarfina; Dedek Nursiti Khodijah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Indonesia's high vulnerability to hydrometeorological disasters highlights the inconsistent implementation of disaster mitigation education in early childhood settings. This study aimed to evaluate the effectiveness of structured role-playing in enhancing disaster preparedness among young children. A classroom action research study based on John Elliott's model was conducted with eight children aged 5–6 years at TAUD Luqmanul Hakim, Langsa, focusing on hazard identification, warning signs, and evacuation procedures. Data were collected through observation, performance rubrics, and field notes, then analyzed using descriptive percentages. Results demonstrated a significant improvement in student mastery, rising from 37% in Cycle I to 100% in Cycle II, categorized as